PENGEMBANGAN INSTRUMEN KEMAMPUAN BERPIKIR ANALISIS SISWA SMP DALAM MENYELESAIKAN SOAL PEMECAHAN MASALAH MATEMATIKA - Irawati, Tri Novita; Mahmudah, Muhlisatul (Kadikma, 2018)
Abstract. This study aimed to describe the process and to develop analytical thinking ability instruments referring to the Thiagarajan Model known as the Four-D Model (Model 4-D). The Thiagarajan Model consists of four stages: define, planning, design, and disseminate stages. Data analysis consisted of instrument validation analysis, instrument reliability, practicality and effectiveness of instruments and analysis of teacher response data on the results of instrument development. Based on the results of the analysis, the instrument developed reached high level of instrument validation by experts with a validity coefficient of 0.748 and high level of instrument reliability with a reliability coefficient of 0.78. In addition, the degree of practicality was in the high category with a degree of coefficient (IP) = 4. It also reached high degree of effectiveness with a degree of coefficient (IE) = 4.6. The teacher's response to the development of the instrument was very good with a teacher response of 90%. Keywords: Analytical thinking skills, problem solving questions